2013
DOI: 10.1002/cncr.28118
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated radiotherapy (IMRT) in pediatric low‐grade glioma

Abstract: BACKGROUND The objective of this study was to evaluate local control and patterns of failure in pediatric patients with low‐grade glioma (LGG) who received treatment with intensity‐modulated radiation therapy (IMRT). METHODS In total, 39 children received IMRT after incomplete resection or disease progression. Three methods of target delineation were used. The first was to delineate the gross tumor volume (GTV) and add a 1‐cm margin to create the clinical target volume (CTV) (Method 1; n = 19). The second was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Most trials however, have used doses ranging from 45‐ 54 Gy in 1.8 Gy per fraction. In HIT LGG 96 trial, no difference was observed between a total dose of 50.4 Gy and 54 Gy and this has been confirmed in other studies . 50.4 Gy in 1.8Gy per fraction is therefore the recommendation on current studies, with doses less than that(45Gy) reserved for younger children (< 5 years of age).…”
Section: Treatmentsupporting
confidence: 57%
See 1 more Smart Citation
“…Most trials however, have used doses ranging from 45‐ 54 Gy in 1.8 Gy per fraction. In HIT LGG 96 trial, no difference was observed between a total dose of 50.4 Gy and 54 Gy and this has been confirmed in other studies . 50.4 Gy in 1.8Gy per fraction is therefore the recommendation on current studies, with doses less than that(45Gy) reserved for younger children (< 5 years of age).…”
Section: Treatmentsupporting
confidence: 57%
“…This margin accounts for set up error and depends on the quality of the immobilisation device, the accuracy of radiotherapy equipment (e.g. gantry, couch and lasers) and the ability of centres to perform portal imaging for geometric verification during treatment . For centres without regular portal imaging for verification, the PTV margin should not be less than 5mm, and where there is any doubt as to any of the accuracy measures above, then the PTV margin should not be less than 10mm.…”
Section: Treatmentmentioning
confidence: 99%
“…concepts currently in use [1,6,[9][10][11][12], ongoing interest exists to further expand the platform of localized treatment concepts for PLGG patients. A previously published pilot study has suggested that low-dose rate stereotactic Iodine-125 brachytherapy (SBT) allowing precise application of ablative tumor doses with maximum sparing of surrounding normal tissues might contribute to the spectrum of localized treatment concepts for complex located PLGGs; in that study SBT was used either alone in case of small-sized unresectable tumors or coupled with best safe resection (in case of larger tumor volumes) and has turned out to be feasible and safe [13].…”
Section: Original Researchmentioning
confidence: 99%
“…In case of incompletely resectable or unresectable tumors, however, PFS becomes significantly shorter leading to the initiation of adjuvant treatment concepts including chemotherapy or radiotherapy relatively early during the history of the disease . Given the non‐negligible risk of short‐ and long‐term side effects of adjuvant treatment concepts currently in use , ongoing interest exists to further expand the platform of localized treatment concepts for PLGG patients. A previously published pilot study has suggested that low‐dose rate stereotactic Iodine‐125 brachytherapy (SBT) allowing precise application of ablative tumor doses with maximum sparing of surrounding normal tissues might contribute to the spectrum of localized treatment concepts for complex located PLGGs; in that study SBT was used either alone in case of small‐sized unresectable tumors or coupled with best safe resection (in case of larger tumor volumes) and has turned out to be feasible and safe .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Chemotherapy is therefore the standard postsurgical modality for young patients with PLGG and is aimed at improving PFS and delaying the use of RT. 10 Improved imaging, along with modern treatment planning and delivery techniques such as 3-dimensional conformal RT (3D-CRT), 11 stereotactic RT, 12,13 intensity modulated RT (IMRT), 14 and proton therapy 15,16 allow the delivery of more conformal treatments for patients with PLGG. The use of tighter treatment volumes is expected to be associated with fewer long-term adverse effects.…”
Section: Introductionmentioning
confidence: 99%